The Role of Dbf4-Dependent Protein Kinase in DNA Polymerase ζ-Dependent Mutagenesis in Saccharomyces cerevisiae. Issue 4 (1st August 2014) - Brandão, Luis N; Ferguson, Rebecca; Santoro, Irma; Jinks-Robertson, Sue; Sclafani, Robert A
Abstract: The yeast Dbf4-dependent kinase (DDK) (composed of Dbf4 and Cdc7 subunits) is an essential, conserved Ser/Thr protein kinase that regulates multiple processes in the cell, including DNA replication, recombination and induced mutagenesis. Only DDK substrates important for replication and recombination have been identified. Consequently, the mechanism by which DDK regulates mutagenesis is unknown. The yeast mcm5 -bob1 mutation that bypasses DDK's essential role in DNA replication was used here to examine whether loss of DDK affects spontaneous as well as induced mutagenesis. Using the sensitive lys2 ΔA746 frameshift reversion assay, we show DDK is required to generate "complex" spontaneous mutations, which are a hallmark of the Polζ translesion synthesis DNA polymerase. DDK co-immunoprecipitated with the Rev7 regulatory, but not with the Rev3 polymerase subunit of Polζ. Conversely, Rev7 bound mainly to the Cdc7 kinase subunit and not to Dbf4 . The Rev7 subunit of Polζ may be regulated by DDK phosphorylation as immunoprecipitates of yeast Cdc7 and also recombinant Xenopus DDK phosphorylated GST-Rev7 in vitro . In addition to promoting Polζ-dependent mutagenesis, DDK was also important for generating Polζ-independent large deletions that revert the lys2 ΔA746 allele. The decrease in large deletions observed in the absence of DDK likely results from an increase in the rate of replication fork restart after an encounter with spontaneous DNA damage. Finally, nonepistatic, additive/synergistic UV sensitivity was observed in cdc7 Δ pol32 Δ and cdc7 Δ pol30 -K127R, K164R double mutants, suggesting that DDK may regulate Rev7 protein during postreplication "gap filling" rather than during "polymerase switching" by ubiquitinated and sumoylated modified Pol30 (PCNA ) and Pol32 .